2011
DOI: 10.36510/learnland.v4i2.388
|View full text |Cite
|
Sign up to set email alerts
|

Stepping-Stone or Saving Story?

Abstract: Why does one enter graduate studies? What does it mean to do research on Indigenous education as an Aboriginal person? What is the significance of attaining a master’s degree? In this paper I speak to how the experience of inquiring into the educational stories of five of my relatives, and into my own lived experiences, helped me understand the importance of stories and the impact of the autobiographical narrative inquiry on myself and my family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Over time, our coming alongside pre-and in-service teachers and inviting them to engage in reflection through ANI has grown increasingly guided by Cardinal (2011), who drew on Wilson (2001) knowledge of "All Our Relations" and "relational accountability" to highlight the significance of the inter-relational dimensions of experience. Cardinal's guidance has grown our understanding of Donald (2009) knowledge of ethical relationality, as well as our ethical responsibilities to the more-than-human, spiritual, and ancestral realms that ground and shape our interactions.…”
Section: Imagining Our Forward Responsibilitiesmentioning
confidence: 99%
“…Over time, our coming alongside pre-and in-service teachers and inviting them to engage in reflection through ANI has grown increasingly guided by Cardinal (2011), who drew on Wilson (2001) knowledge of "All Our Relations" and "relational accountability" to highlight the significance of the inter-relational dimensions of experience. Cardinal's guidance has grown our understanding of Donald (2009) knowledge of ethical relationality, as well as our ethical responsibilities to the more-than-human, spiritual, and ancestral realms that ground and shape our interactions.…”
Section: Imagining Our Forward Responsibilitiesmentioning
confidence: 99%
“…Claypool and Preston (2011), similarly beginning with emphasis on how "the learning and assessment of Aboriginal students remains subjugated by a Western perspective" (p. 84), showed that while there has been some movement in Canada toward "insuring Aboriginal content (including Treaty education), resources and ways of knowing are infused into curriculum" a key overlooked aspect is that in addition to "refining curricula to incorporate Aboriginal voice and identity, student learning and assessment techniques need to parallel Aboriginal worldviews and ways of knowing" (p. 85). relational aspects of our inquiry with the pre-and in-service teachers in the course we, individually and collectively, experienced Trudy's (Cardinal, 2011) description of a "space for inquiry into our stories" (p. 80) where "more than merely living out research is at work . .…”
Section: Living Our Commitments As Relational Narrative Inquirersmentioning
confidence: 99%
“…4. Given the focus and space restrictions of this article, we suggest that if readers are interested in more detailed accounts of how other narrative inquirers have inquired into the stories they are living and telling, they read the proceeding autobiographical narrative inquiries (see Caine, 2010;Cardinal, 2011;Casey & Schaefer, 2016;Dubnewick, 2016;Dubnewick, Fox, & Clandinin, 2013;Huber, Li, Murphy, Nelson, & Young, 2014;Saleh, Menon, & Clandinin, 2014).…”
Section: Fundingmentioning
confidence: 99%